Faber Method Classical Piano Learning In Purwacaraka Music School Purwokerto - Utami, Nur Aini Putri; Widjajantie, Kusrina (Jurnal Seni Musik, 2020)
Purwacaraka Purwokerto Music School is able to give birth to talented classical piano students so they can win various championships. From the observations, this is influenced by the use of the faber method in learning. This study aims to describe learning methods faber at Purwacaraka Purwokerto Music School. The research approach applied in this study is descriptive qualitative. Data collection techniques are carried out by observation, interview and document study. The results of this study indicate that the use of the faber method in classical piano learning in Purwacaraka Purwokerto Music School is only used at the beginner level (Grade Preparatory) and is an excellent method for learning at the beginner level because it uses books specifically designed for beginners with many bring up colorful images that make students imagine, so students understand learning material in their own way. The advantages of the faber method are that students get a strong foundation in reading beam notation, dynamics games and articulation in a score of songs played and this method is a very good method used as a basis for learning piano because it has material and theory that is emphasized to provide basic reference piano playing with piano playing techniques.